Quantitative chemical analysis of perovskite deposition using spin coating - Peter Holliman (Materials Letters: X, 2019)
Lead and halide ion compositions of spin coated organo-lead halide perovskite films have been quantifiedusing ion chromatography (IC) and atomic absorption spectroscopy (AAS) using perovskite films manu-factured by 5 different researchers (3 replicates per treatment) to monitor variability between research-ers and individual researcher reproducibility. Planar and mesoporous TiO2-coated glass substrates havebeen studied along with tribromide (CH3NH3PbBr3), triiodide (CH3NH3PbI3) and mixed halide(CH3NH3PbI3xClx) perovskite films. The data show low yields of spin coated perovskite material (ca.1%) and preferential deposition of Iover Clin mixed halide films.